2020
DOI: 10.3390/app10062069
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Oxygen Saturation Monitoring during Spinal Surgery in Order to Identify Patients at Risk for Cerebral Desaturation

Abstract: Featured Application: The aim of our study was to evaluate the usefulness of intraoperative cerebral oxygenation monitoring during spinal surgery. Study includes specifically spinal neurosurgical patients, as spinal surgery, being performed in prone position, carries a certain risk for altered cerebral blood perfusion and oxygen supply. As a result, we show a benefit of cerebral oxygen saturation non-invasive intraoperative monitoring using Near infrared spectroscopy devices cerebral oximeters as in couple of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…However, the disadvantage of that study was that there was no control group to compare the results (12). Therefore, in our study, as a control group, we also had the septoplasty group in which the head is kept in the neutral position when performing ear effect on cerebral hypoxia, but it was emphasized that the amount of blood loss was significantly effective (24). We consider that the non-significant effect of the operation time was due to the prone positioning of the patients and the neutral positioning of the head throughout the operation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the disadvantage of that study was that there was no control group to compare the results (12). Therefore, in our study, as a control group, we also had the septoplasty group in which the head is kept in the neutral position when performing ear effect on cerebral hypoxia, but it was emphasized that the amount of blood loss was significantly effective (24). We consider that the non-significant effect of the operation time was due to the prone positioning of the patients and the neutral positioning of the head throughout the operation.…”
Section: Discussionmentioning
confidence: 98%
“…It is possible to state that there are contradictory statements on this subject in the literature. Some studies have reported that there is no correlation between c-rSO 2 and other intraoperatively monitored parameters such as MABP, SaO 2 , and EtCO 2 (24). In contrast, in another study conducted with ESS patients, it was emphasized that although controlled hypotensive anesthesia alone was a risk for cerebral desaturation, there was no risk of cerebral desaturation if MAP was >55 mmHg, EtCO 2 was 30-40, and the head was kept in the neutral position (8).…”
Section: Discussionmentioning
confidence: 99%